PERBEDAAN EFEKTIVITAS CONSTRUCTED WETLANDSSUBSURFACE FLOW SYSTEM DAN FREE WATER SURFACE PADATANAMAN CATTAIL UNTUK MENURUNKAN BOD, COD dan FOSFAT LIMBAH LAUNDRY DI KELURAHAN TEMBALANG, KOTA SEMARANG - Miftah Hermaning Putri; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Small laundry industry is activities that related in laundering services. Laundry wastewater directly disposed into sewerage without treatment. The checking result of BOD, COD and phosphate of laundry waswater is 260,3 mg/l, 832,9 mg/l, and 10,83 mg/l this number is exceed the standard of Perda Jateng No 5 2012 th. The study research is using quasi experiment (quasi experiment) with pre test - post test design.The research objects are the laundry liquid wastes from